Chapter 9. Essential oils in pig diet as a means of improving pork quality - Prudyus, Taras; Vishchur, Oleg; Danchenko, Mykola; Данченко, Микола Миколайович (Scientific Route Tallinn Estonia, 2025)
EN: The conducted study of the influence of the feed additive "Activo" on the physico chemical properties and fatty acid composition of the liver and meat of pigs allowed to detect significant changes in lipid metabolism, which contributes to the improve ment of the quality characteristics of the meat. In the meat of pigs of the experimen tal group, a significantly lower content of peroxide oxidation products was found. Analy sis of the fatty acid composition of the liver of pigs proved that the use of the feed additive contributed to a change in the profile of saturated, monounsaturated and polyunsaturated fatty acids. In the meat of pigs of the experimental group, a de crease in the level of stearic and pentadecanoic acids was found, while an increase in the level of monounsaturated fatty acids, in particular oleic acid, was recorded, which con tributes to positive changes in the organoleptic characteristics of the meat. The results obtained allow to conclude that the addition of the feed additive "Activo" affects lipid metabolism in pigs, changing the balance of fatty acids in the liver and muscles, and also contributes to the inhibition of oxidative damage to the lipid component of meat. The detected changes positively affect the quality of meat, in particular its antioxidant status, heat resistance and organoleptic properties. /// UA: Проведене дослідження впливу кормової добавки "Activo" на фізико-хімічні властивості та жирнокислотний склад печінки та м'яса свиней дозволило виявити значні зміни ліпідного обміну, що сприяє поліпшенню якісних характеристик м'яса. У м'ясі свиней дослідної групи виявлено значно менший вміст продуктів перекисного окислення. Аналіз жирнокислотного складу печінки свиней довів, що застосування кормової добавки сприяло зміні профілю насичених, мононенасичених і поліненасичених жирних кислот. У м'ясі свиней дослідної групи виявлено зниження рівня стеаринової та пентадеканової кислот, при цьому було зафіксовано підвищення рівня мононенасичених жирних кислот, зокрема олеїнової кислоти, що сприяє позитивним змінам органолептичних показників м'яса. Отримані результати дозволяють зробити висновок, що додавання кормової добавки «Activo» впливає на ліпідний обмін у свиней, змінюючи баланс жирних кислот в печінці і м'язах, а також сприяє гальмуванню окисного пошкодження ліпідної складової м'яса. Виявлені зміни позитивно впливають на якість м'яса, зокрема на його антиоксидантний статус, термостійкість та органолептичні властивості.
Розділ 9. Ефірні масла в раціоні свиней як засіб поліпшення якості свинини
Keywords: pork; feed additive; fatty acid composition; essential fatty acids; ω-3 and ω-6 fat ty acids; oxidative spoilage; organoleptic properties; свинина; кормова добавка; жирнокислотний склад; незамінні жирні кислоти; ω-3 і ω-6 жирні кислоти; окислювальна псування; органолептичні властивості